Extending the Class of [1, 3]‐Dioxolo[4.5‐f]benzodioxole (DBD) Fluorescent Dyes. Issue 14 (16th April 2018) - Wessig, Pablo; John, Leonard; Mertens, Monique
Abstract : Synthetic routes to a collection of new fluorescent dyes are described, which are based on the [1, 3]‐dioxolo[4.5‐ f ]benzodioxole (DBD) core. By introducing different electron withdrawing groups in 4‐ and 8‐position of the DBD moiety the emission wavelength could be adjusted over a large spectral range from blue to orange light. Abstract : A synthetic methodology for the variation of electron withdrawing groups in DBD fluorescent dyes has been established. Thus, the emission wavelength can be varied over a wide range.